Multimodal Analysis of STRADA Function in Brain Development - Dang, Louis T.; Glanowska, Katarzyna M.; Iffland II, Philip H.; Barnes, Allan E.; Baybis, Marianna; Liu, Yu; Patino, Gustavo; Vaid, Shivanshi; Streicher, Alexandra M.; Parker, Whitney E.; Kim, Seonhee; Moon, Uk Yeol; et al. (Frontiers in Cellular Neuroscience, 2020)
mTORopathies are a heterogeneous group of neurological disorders characterized by malformations of cortical development (MCD), enhanced cellular mechanistic target of rapamycin (mTOR) signaling, and epilepsy that result from mutations in mTOR pathway regulatory genes. Homozygous mutations (del exon9-13) in the pseudokinase STE20-related kinase adaptor alpha (STRAD-α; STRADA), an mTOR modulator, are associated with Pretzel Syndrome (PS), a neurodevelopmental disorder within the Old Order Mennonite Community characterized by megalencephaly, intellectual disability, and intractable epilepsy. To study the cellular mechanisms of STRADA loss, we generated CRISPR-edited Strada mouse N2a cells, a germline mouse Strada knockout (KO; -/-) strain, and induced pluripotent stem cell (iPSC)-derived neurons from PS individuals harboring the STRADA founder mutation. Strada KO in vitro leads to enhanced mTOR signaling and iPSC-derived neurons from PS individuals exhibit enhanced cell size and mTOR signaling activation, as well as subtle alterations in electrical firing properties e.g., increased input resistance, a more depolarized resting membrane potential, and decreased threshold for action potential generation. Strada-/- mice exhibit high rates of perinatal mortality and only 8 animals have survived past P5. Strada-/- mice are hypotonic and tremulous. Histopathological examination (n=5 mice) revealed normal gross organization and lamination but all had ventriculomegaly. Ectopic neurons were seen in all 5 Strada-/- brains within the subcortical white matter mirroring what is observed in human PS brain tissue. These distinct experimental platforms demonstrate that STRADA modulates mTOR signaling and is key regulator of cell size, neuronal excitability, and cortical lamination.